Anxiety level in overweight and obese children - M.L. Aryayev; D.S. Selimkhanova; I.M. Shevchenko (Український журнал Перинатологія і педіатрія, 2023)
Purpose - to evaluate personal and situational anxiety levels in overweight and obese children.